Healthy placemaking : wellbeing through urban design - London, Fred (London : RIBA Publishing, 2020)
In modern-day society the main threats to public health are now considered 'avoidable illnesses', which are often caused by a lack of exercise and physical activity. Research suggests that architectural and urban design strategies play an important role in reducing the amount of avoidable illnesses by enabling physical activity through healthier streets. Practitioners must now consider how they can encourage people to lead healthier lifestyles and improve health through urban design. This book presents the path to healthier cities through six core themes - urban planning, walkable communities, neighbourhood building blocks, movement networks, environmental integration and community empowerment. Each theme is presented with an overview of the issues, the solutions and how to apply them practically with exemplars and precedents. It's an essential text that provides practitioners across urban design, architecture, master planning with the necessary knowledge and guidance to understand their role in producing healthier places and put it in to practice.
Human nature and health -- Health at the heart of planning -- From theory to practice -- Where next?
OCLC-licensed vendor bibliographic record.
Keywords: City planning -- Health aspects; Public health; Urban health; Community development; ARCHITECTURE / General; ARCHITECTURE / Urban & Land Use Planning